Hospital Dispute Settlement Through the Provincial Hospital Supervisory Board in Indonesian Health Law (A Study in Yogyakarta Province) - Alawiya, Nayla; Utami, Nurani Ajeng Tri; Afwa, Ulil (Jurnal Dinamika Hukum, 2023)
Hospitals as health service institutions with legal entities are places that are prone to disputes. Article 60 Law no. 44 of 2009 assigned the Provincial Hospital Supervisory Board to receive complaints and make efforts to resolve disputes employing mediation. An analysis of the forms of hospital disputes and their settlement model through the Provincial Hospital Supervisory Board is very important to be done to avoid misinterpretation and provide legal certainty about who is the authorized party to handle them. The research method used was normative juridical and empirical juridical. The results of this study are to obtain an analysis of the forms of complaints that can be submitted to the Provincial Hospital Supervisory Board including disputes over hospitals as health service facilities where medical personnel and health workers provide health services that are detrimental to patients; disputes between the hospital as a health service facility and the patient as the recipient of health services related to the implementation of the obligations of both parties; disputes between the hospital as a legal entity and the hospital workforce related to internal management; the disputes between hospital as a legal entity and the third parties related to non-medical cooperation; the disputes between hospital as a legal entity and the environment. The hospital dispute resolution model implemented by the Provincial Hospital Supervisory Board of Yogyakarta includes the hospital dispute resolution model by the Provincial Hospital Supervisory Board in collaboration with hospitals, the Hospital Supervisory Board, Provincial Health Office, Provincial Legal Representatives (Ombudsman), YLKI, and PERSI.Keywords: Provincial Hospital Supervisory Board, Disputes Form, Dispute Settlement Model.